EXPRESSIVE AND EVALUATIVE POTENTIAL OF IDIOMS OF GAMBLING IN SPANISH - Bobchynets , Lyubov (PROBLEMS OF SEMANTICS, PRAGMATICS AND COGNITIVE LINGUISTICS, 2022)
The research paper is dedicated to functional analysis of the idioms of gambling in Contemporary Spanish. The studied phraseological units are frequently used in texts of news, in particular, in the titles. There are few cases of the use of Spanish lexicon of gambling as proper names: ergonyms and names of plates. The idioms of gambling in the Spanish language perform expressive and evaluative functions. The main method of our research is the contextual analysis which reveals positive or negative evaluation of people, situations and behavior, expressed by the idioms of gambling. The most part of phraseological units of gambling are used to characterize negatively politicians and their actions. The proverbs and sayings about gambling in Spanish express negative evaluation of the game which may cause addiction. According to the structure, the idioms of gambling are nominative, attributive and verbal word combinations. The proverbs and sayings about gambling are simple and compound sentences with rhyme and parallel structure. According to the origin, the studied idioms are international or borrowed from other languages, as the English borrowing "poker face", and national idioms which mainly refer to Spanish playing cards, as "echar un órdago", "cantar las cuarenta", etc. The future studies may be devoted to the search of right equivalents of translation of the Spanish idioms of gambling into Ukrainian and comparative linguistic and culture studies of Spanish and Ukrainian idioms of gambling. __________ References: • Almargo, «Rafa Escobar enseña sus cartas hoy en Estepona». Europasur. Accessed August 03, 2012. http://www.europasur.es/deportes/Rafa-Escobar-ensena-cartas-Estepona_0_612239349.html • De Haro, José Luis. «La Fed no enseña sus cartas ante la incertidumbre de Trump y una creciente inflación». El economista. Accessed February 01, 2017. http://www.eleconomista.es/mercados-cotizaciones/noticias/8126391/02/17/La-Fed-no-ensena-sus-cartas-ante-la-incertidumbre-de-Trump-y-una-creciente-inflacion.html • Díaz Orozco, Zuluaga Gómez, F. O., Astrid Ciro, L. «Funciones de los fraseologísmos en la novelística de García Márquez: el caso de la desautomatización.» Revista virtual Universidad Católica del Norte, (26), febrero-mayo, 2009. Accessed September 03, 2022: http://revistavirtual.ucn.edu.co/index.php/RevistaUCN/article/view/112 • González Díaz, José Luis. Dichos y proverbios (Madrid: Edimat Libros, 2013), 490. • Jerico, Pilar. Ante los problemas de una mujer el hombre da soluciones y pone cara de póquer. Accessed November 03, 2015. http://www.pilarjerico.com/por-que-ante-los-problemas-de-una-mujer-el-hombre-da-soluciones-y-pone-cara-de-poquer • Körbely, Rörs, S, F. "Rusia vuelve a meter baza en Afganistán". Tiempo de hoy. Accessed May 05, 2017. http://www.tiempodehoy.com/mundo/rusia-vuelve-a-meter-baza-en-afganistan • Lozano, "El as en la manga que se guardaba el chavismo para fijar sus propias reglas". La Nación. Accessed May 03, 2017. http://www.lanacion.com.ar/2019921-el-as-en-la-manga-que-se-guardaba-el-chavismo-para-fijar-sus-propias-reglas • Parra, Ignacio. Autoestima es el castillo de naipes. Accessed May 18, 2015. http://www.psicologomajadahonda.net/autoestima-el-castillo-de-naipes/ • Romero, Yolando. "Romper la baraja". Accessed September 20, 2013. http://www.judoaviles.es/actualidad-noticias-detalle.asp?id=408 • Zuluaga, A. Sobre las funciones de los fraseologismos en los textos literarios (Madrid: Paremia, 1997): 631-640. • «A Madrid jugárselo todo». Accessed April 21, 2017. http://www.judoaviles.es/actualidad-noticias-detalle.asp?id=408 • «Baraja de viajes». Accessed November 23, 2016. https://barajadeviajes.com/2016/11/23/el-parque-tayrona-en-colombia/ • «El nuevo partido de Clolau enseña sus cartas: república social, democrática y ambientalmente justa». abc.es Accessed January 20, 2017. http://www.abc.es/espana/catalunya/politica/abci-nuevo-partido-colau-ensena-cartas-republica-social-democratica-y-ambientalmente-justa-201701201241_noticia.html • «Jugárselotodo». Hoy es. noticias de deporte. Accessed November 09, 2013. http://www.hoy.es/v/20111109/deportes/mas-deporte/golf-normal-jugarselo-todo-20111109.html • «Taberna Sota, caballo, rey: el nuevo concepto del grupo Raza Nostra en Pozuelo». Blogpost Comer bien a buen precio en Madrid. Accessed June 28, 2015 http://comerbienabuenpreciomadrid.blogspot.com/2015/06/sota-caballo-rey-raza-vaca-hamburguesa-nostra-juan-pozuelo.html